Superparamagnetic iron oxide nanoparticles (SPIONs) modulate hERG ion channel activity. Issue 9 (21st October 2019) - Gualdani, Roberta; Guerrini, Andrea; Fantechi, Elvira; Tadini-Buoninsegni, Francesco; Moncelli, Maria Rosa; Sangregorio, Claudio
Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) are widely used in various biomedical applications, such as diagnostic agents in magnetic resonance imaging (MRI), for drug delivery vehicles and in hyperthermia treatment of tumors. Although the potential benefits of SPIONs are considerable, there is a distinct need to identify any potential cellular damage associated with their use. Since human ether à go-go-related gene (hERG) channel, a protein involved in the repolarization phase of cardiac action potential, is considered one of the main targets in the drug discovery process, we decided to evaluate the effects of SPIONs on hERG channel activity and to determine whether the oxidation state, the dimensions and the coating of nanoparticles (NPs) can influence the interaction with hERG channel. Using patch clamp recordings, we found that SPIONs inhibit hERG current and this effect depends on the coating of NPs. In particular, SPIONs with covalent coating aminopropylphosphonic acid (APPA) have a milder effect on hERG activity. We observed that the time-course of hERG channel modulation by SPIONs is biphasic, with a transient increase (∼20% of the amplitude) occurring within the first 1–3 min of perfusion of NPs, followed by a slower inhibition. Moreover, in the presence of SPIONs, deactivation kinetics accelerated and the activation and inactivation I–V curves were right-shifted, similarly to the effect described for the binding of other divalent metal ions (e.g. Cd 2+ and Zn 2+ ). Finally, our data show that a bigger size and the complete oxidation of SPIONs can significantly decrease hERG channel inhibition. Taken together, these results support the view that Fe 2+ ions released from magnetite NPs may represent a cardiac risk factor, since they alter hERG gating and these alterations could compromise the cardiac action potential.